Assessment of sensitivity and accuracy of BEM-based aeroelastic models on wind turbine load predictions. Issue 4 (September 2020) - Caboni, M.; Carrion, M.; Rodriguez, C.; Schepers, G.; Boorsma, K.; Sanderse, B.
Abstract: The general goal of the work reported in this paper is to gain more confidence when performing blade element momentum (BEM)-based aeroelastic simulations, especially when setting-up sub-models and their parameters. Due to limited or no information, the set-up of these methods is often highly uncertain. To achieve this objective, we have developed and used methodologies to perform the analysis of model uncertainty in wind turbine aeroelastic simulations, while assessing their accuracy. This paper presents an example where these methodologies have been applied to a) the different aerodynamic models used in BEM-based aeroelastic tools to account for unsteady airfoil aerodynamics (UAA) and b) key parameters used in one of these models (Beddoes-Leishman). The accuracy of the simulations is assessed by comparing the simulated unsteady loads with measurements from the DAN-AERO MW experiments. One of the main achievements of this work is the ability to assess the uncertainty in load predictions that derives from the uncertainty related to the UAA models and their constants. The study on the sensitivity of the parameters was performed using Sobol indices and showed that for the case under study the normal force standard deviation at outboard blade locations is mostly sensitive to the Beddoes-Leishman model's vortex shedding time constant.